Permafrost livelihoods: A transdisciplinary review and analysis of thermokarst-based systems of indigenous land use. (June 2017) - Crate, Susan; Ulrich, Mathias; Habeck, J. Otto; Desyatkin, Aleksey R.; Desyatkin, Roman V.; Fedorov, Aleksander N.; Hiyama, Tetsuya; Iijima, Yoshihiro; Ksenofontov, Stanislav; Mészáros, Csaba; Takakura, Hiroki
Highlights: Sakha (Yakuts) have used thermokarst areas for animal husbandry for at least the last half millennium. Climate change is transforming thermokarst ecosystems at an unprecedented rate. An interdisciplinary assessment of thermokarst dynamics and land use in view of climate, demographic and economic change is presented. Abstract: In a context of scientific and public debates on permafrost degradation under global climate change, this article provides an integrated review and analysis of environmental and socio-economic trends in a subarctic region. It focuses on Sakha (Yakut) animal husbandry as an example of indigenous land use. Within Sakha-Yakutia's boreal forests, animal husbandry takes place in thermokarst depressions containing grassland areas (alaas) that formed in the early Holocene in a complex interplay of local geological conditions, climate changes, and permafrost dynamics. The current scale and speed of environmental change, along with shifting socio-economic processes, increasingly challenges Sakha's adaptive capacity in use of alaas areas. The paper synthesizes information on the evolution of permafrost landscapes and on the local inhabitants' and scientific knowledge. It also probes land-use prospects for the near future. The imminence of challenges for alaas ecosystems requires a holistic understanding between researchers and stakeholder communities, which in turn depends on a comprehensive assessment of the dynamic interaction of physical and social drivers of change.